(untitled) (Quest Journal of Management and Social Sciences, 2021)
Background: The relationship between population and economic growth has always been a subject of debate. There has never been any clear consensus amongst economists about the nature and extent of influence that population has on the economic growth of a country. Objective: This paper aims to explore the influence exerted by the age structure of the population on the economic growth of a country. Method: The paper uses secondary data to find the relation between Gross Domestic Product (GDP) per capita levels of countries and their respective Age Dependency Ratio. Result: There is a significant negative relationship between them, which implies that, if a country has a rise in a high proportion of the dependent population, per capita income will tend to be lower. Conclusion: The paper then makes a special study of the prospect of demographic dividend in India. The country is in the third phase of demographic transition, implying that the proportion of the working-age population is greater than the dependent population. This provides an ideal condition for the Government to reap the benefits of demographic dividend and achieve higher levels of economic growth.